Applications of geothermal sources for absorption chillers as efficient and clean cooling technologies for buildings: A comprehensive review - Alhuyi-Nazari M.; Mukhtar A.; Yasir A.S.H.M.; Ahmadi M.H.; Kumar R.; Luong T.N.L. (Elsevier Ltd, 2025)
Population growth in hot and arid regions in addition to global warming would lead to increase for cooling demand in near future. Corresponding to energy consuming nature of cooling processes, and consequently emissions of greenhouse gases, it is crucial to use clean energy technologies for cooling purposes. Absorption chiller is one of the cooling technologies with ability of producing cooling by using medium or low-temperature heat sources. Employment of absorption chillers for cooling production can lead to electricity saving and reduction of pollutants emissions. These technologies could be cost effective options for cooling of large-scale buildings and district cooling systems. In order to make these systems more environmentally benign, renewable energy technologies can be coupled with these systems. It is possible to apply thermal energy extracted from geothermal energy source instead of combustion of fossil fuels as absorption chillers heat source to have cleaner technologies. This paper reviews the research works on the applications of geothermal sources for absorption chillers. In order to find the relevant studies appropriate for this review article, GoogleScholar, Scopus and websites of scientific publishers are used. The factors influencing the performance of geothermal absorption chillers in addition to the hybrid and polygeneration systems composed of geothermal absorption chillers are considered in this review article. From the results of the reviewed studies it is concluded that performance of absorption chillers using geothermal sources is dependent on different factors such as the configuration of system, operating condition, mass flow rate of geofluid and applied components. Moreover, it is seen that it is possible to integrate other geothermal systems, i.g. power production units, with absorption chillers to simultaneously produce cooling. Furthermore, some scholars have applied solar energy in addition to geothermal in these systems to achieve more gain from the renewable energy sources. ? 2023 Elsevier Ltd